Evaluation of Safety Risk Management Systems on Upper Structure Work of LRT Cawang – Dukuh Atas Project - Mulyo, Yusak Sabdono; Puro, Sarjono; Fahruroji, Aan Fa'alil (Media Teknik Sipil, 2020)
Light Rail Transit (LRT) Segmen Cawang – Dukuh Atas Project which is under construction by PT. Adhi Karya Tbk contents a high potency to any work accident occurance. This research is intended to evaluate the implementation of Safety Risk Management System by PT. Adhi Karya Tbk by identifying/assessing the grade of the implementation and make an evaluation wether something needs to be improved. The method used  is descriptive analysis then suitability assessment is based on Australian Standard/New Zealand Standard (AS/NZS) ISO 31000 : 2009. The secondary data obtained from QHSE Railways Departement of PT. Adhi Karya Tbk and primary data is taken from interview or questionnaires to employees. Based on data and qualitative analysis shows that suitability based on AS/NZS ISO 31000:2009 is 90%, risk of work accident can be well controlled  without reducing productivity. Suggestion for next improvements needed are to standardize that all of K3 personnels must be certified, and keep the implementation of Safety Risk Management System consistently.